Chemical darkrooms: Three architectural design experiments for surreal metamorphoses of body and photography. (1st December 2013) - Loizos, Yorgos
Central to my research is the collapse of nature, technology and the human body as a both creative and critical way for speculating architectures of constant change. Photography and film have been essential for recording these changes, and in many cases these arts have even allowed to register a world beyond our perception. The article focuses on Surrealist artist Man Ray and his contemporary artists, photographers and film-makers who saw the chemical photography's potential through the alchemic transformation of light and dark throughout their devices, films and darkroom methods. In parallel the article links with architectural design and theory, with a series of design experiments through chemical photographic and analogue processes, to challenge and re-inspire a more contemporary digital architecture. This article will investigate chemical photography of its variable density and indices as a new form of constructing architectures. How the wet process of chemical photography could advance in such a way that could become architectural, and by exploring the light and temperature sensitive aspect of space, will evoke its constant transmutation and openness to chance.